Quotas rural employees in public higher education: un analytical panorama - Gois, Pamela Karina de Melo; Pereira Júnior, Ednaldo Barbosa; Ximenes, Jedson Machado (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2019)
The Quota Law, apart from its social contour, deals with ethnic-racial criteria and allows institutions, based on their particular social reality, to use, as affirmative action, the creation of a reserve of vacancies, aiming at benefitting other minority groups. This article, therefore, aims at analyzing the policy related to the reserving vacancies for children belonging to PRONAF families, settlers of agrarian reform and rural employees who are taking up Public Higher Education. In addition, it aims both at discussing the legal bases concerning this affirmative action, in order to identify the Public Institutions that adopt this quotas policy, and at presenting the offered courses as well as the number of vacancies reserved for rural students. As to its methodological procedure, it was based both on qualitative/ quantitative research, and on indirect and descriptive documentation. The results show that the adoption of the Quotas Law represented an undeniable advance in terms of democratization, taking into consideration the access to the once historically excluded groups. It is important to point out, however, that there are only few institutions adopting such system and benefitting children who belong to PRONAF families, settlers of agrarian reform and rural employees. They are only 3 in Brazil, Federal Institutes of Education, science and technology of Paraíba, Tocantins and southeast of Minas Gerais. Besides, they belong to specific Campuses and are mostly related to courses which are directed to the rural area.